The pretubulysin-induced exposure of collagen is caused by endothelial cell retraction that results in an increased adhesion and decreased transmigration of tumor cells - Schwenk, Rebecca (Oncotarget, 2017)
Microtubule-targeting agents (MTAs) are the most widely used chemotherapeutic drugs. Pretubulysin (PT), a biosynthetic precursor of the myxobacterial tubulysins, was recently identified as a novel MTA. Besides its strong anti-tumoral activities, PT attenuates tumor angiogenesis, exerts anti-vascular actions on tumor vessels and decreases cancer metastasis formation in vivo. The aim of the present study was to analyze the impact of PT on the interaction of endothelial and tumor cells in vitro to gain insights into the mechanism underlying its anti-metastatic effect. The influence of PT on tumor cell adhesion and transmigration onto/through the endothelium as well as its influence on cell adhesion molecules and the chemokine system CXCL12/CXCR4 was investigated. Treatment of human endothelial cells with PT increased the adhesion of breast cancer cells to the endothelial monolayer, whereas their transmigration through the endothelium was strongly reduced. Interestingly, the PT-induced upregulation of ICAM-1, VCAM-1 and CXCL12 were dispensable for the PT-evoked tumor cell adhesion. Tumor cells preferred to adhere to collagen exposed within PT-triggered endothelial gaps via β1-integrins on the tumor cell surface. Taken together, our study provides, at least in part, an explanation for the anti-metastatic potential of PT.